5(3x − 4) = 1
Which of the following correctly shows the first two steps to solve this equation?
Step 1: 15x − 20 = 1; Step 2: 15x = 21
Step 1: 15x − 4 = 1; Step 2: 15x = 5
Step 1: 8x + 1 = 1; Step 2: 8x = 0
Step 1: 8x − 9 = 1; Step 2: 8x = 10
Answer:
The first choice is the correct answer
Step-by-step explanation:
The value of x is 130° and that of y is 130° as AB and CD are parallel lines.
Parallel lines in geometry are two lines in the same plane that are at equal distance from each other but never intersect. They can be both horizontal and vertical in orientation. Parallel lines can be found in everyday life, such as zebra crossings, notepad lines, and railway tracks. Two lines (in the same plane) are said to be parallel if they never collide, regardless matter how far they are extended on either side. Parallel lines travel parallel to each other, like train tracks.
Here,
x=180-50
x=130°
x=y
y=130°
Because AB and CD are parallel lines, the value of x is 130° and the value of y is 130°.
To know more about parallellines,
#SPJ1
Thank you soooo much!!!!
3$
2 sticks=3 lolipops
1 stick=1.5$. so 1.50$ is left
1 lollipop=1$. so 2$ r left.
what is the solution to the system of equations
2x + 6y = -6 ...(1)
4x - 3y = -12 ...(2)
We can use the method of substitution or elimination to find the solution. I will use the method of substitution.
From equation (1), we can solve for x in terms of y:
2x = -6 - 6y
x = (-6 - 6y)/2
x = -3 - 3y
Now, substitute this value of x into equation (2):
4(-3 - 3y) - 3y = -12
-12 - 12y - 3y = -12
-15y = 0
y = 0
Substitute this value of y back into equation (1) to find x:
2x + 6(0) = -6
2x = -6
x = -3
Therefore, the solution to the system of equations is x = -3 and y = 0.
hope this helps
Answer:
x = -3, y = 0
Step-by-step explanation:
2x+6y=-6 equation1
4x-3y=-12 equation2
multiply equation2 by 2
2[ 4x-3y=-12]
8x - 6y = -24 equation3
add equations 1 & 3
2x+6y=-6
8x - 6y = -24
--------------------
10x = -30
x = -3
substitute x = -3 to any of the equations
I will use equation1
2x+6y=-6
2(-3) + 6y = -6
-6 + 6y = -6
6y = 0
y = 0